Development of Mathematical Snakes and Ladders Media Game Based Learning Approach to Improve Learning Outcomes Class 2 Primary School Students - Reni Angraini; Siti Aisyah; Adriantoni Adriantoni (FKIP - Universitas Riau, 2026)
This study aimed to develop a Mathematics Snakes and Ladders learning media that is valid, practical, and effective in improving the learning motivation and mathematics achievement of second-grade elementary school students. The study employed a Research and Development (R&D) approach using the ADDIE model: analysis, design, development, implementation, and evaluation. The analysis stage identified students’ difficulties in understanding addition concepts up to 20 and the lack of interactive learning media. The design and development stages produced a Mathematics Snakes and Ladders game board, question cards, answer cards, punishment cards, worksheets, and a teacher guidebook. Validation results showed that the media was categorized as Very Valid, with material validation scores of 92.8% and 90.9%, language validation of 92.8%, and media validation of 87.5%. The implementation stage demonstrated high practicality, with teacher practicality scores of 4.60 and 4.73, student responses of 93.2%, and prototype feasibility percentages ranging from 92.00% to 97.33%. Evaluation results showed significant improvement in students’ achievement, with average pretest and posttest scores increasing from 44.00 to 81.33. The N-Gain score reached 0.92 (High category), while classroom observations obtained 98% feasibility. These findings indicate that the media is feasible, practical, and effective for elementary mathematics learning.